Think Pair and Share for Junior High School Students' Reading Comprehension - Siti Nurbaya; Wahyuni Fitria (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2017)
Abstrak The objectives of this study was to find out whether or not there was a significant effect of the using Think-Pair and Share technique at seventh grade students’ reading comprehension of Junior High School Satu Atap Bertam. This research was conducted at first grade students of Junior high school Satu Atap Bertam. This school is located in Muaro Jambi, there are two classes of seventh grade students, and this school uses school based curriculum. In conducting the research, the writer used the experimental research, and the design of the experimental research was a quasi-experimental research. The result of the research found two things: First, the writer has computed the two means score by using t -test formula; the value of t-test was higher than the value of t-table. It indicated that there was a different on the students’ reading comprehension that was taught by using Think Pair and Share technique. Second, the result of the analysis indicated there was a significant difference between the students’ reading comprehension taught by using Think Pair and Share technique and those who were not. Keywords: Think-Pair and share technique; reading comprehension